Pengaruh Efektifitas Pembelajaran Micro Teaching Dan Pengenalan Lapangan Persekolahan II (PLP II) Terhadap Kecakapan Mahasiswa Menjadi Guru - Rani Fasha; Tutut Suryaningsih (Yayasan Al-Afif, 2025)
This study aims to determine the effect of the effectiveness of Micro Teaching and School Field Introduction Program II (PLP II) on students’ teaching competence. The subjects of this research were eighth-semester students of the Economic Education Study Program at Universitas Bhinneka PGRI in the 2024/2025 academic year. This study employed a quantitative approach with data collected through questionnaires from 79 respondents. Data were analyzed using multiple linear regression. The results showed that: (1) Micro Teaching, when examined partially, did not have a significant effect on students’ teaching competence, whereas PLP II did have a significant effect; (2) simultaneously, both variables had a significant impact on students’ teaching competence; (3) the contribution of both variables to students’ teaching competence was 61.2%, with the remaining variance influenced by other factors. These findings highlight the importance of optimizing the implementation of PLP II to enhance students’ readiness to become competent teachers.